2021
DOI: 10.1111/jocn.16120
|View full text |Cite
|
Sign up to set email alerts
|

Self‐care behaviours and related cultural factors among Chinese immigrants with cardiovascular disease in western countries: an integrative review

Abstract: Aims and objectives This review aimed to demonstrate the self‐care behaviours of first‐generation Chinese immigrants with cardiovascular disease in western countries and identify related cultural factors. Background Self‐care is the cornerstone to mitigate disease symptoms and maintain health status. Chinese immigrants to western countries, operating within a cross‐cultural context, may find self‐care to manage their cardiovascular disease challenging. Design An integrative review was conducted. Methods Seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The CADE-Q SV has proven to be both adaptable and useful for multiple language groups; therefore, it is a good instrument to consider for further adaptation to other languages and, now, other immigrant populations 24,49–51 . Given the rapid growth of the Chinese and other immigrant populations in global migration, it is increasingly crucial that instruments be translated and validated in suitable samples, including language groups that have different backgrounds 3,52 . For example, in this study, we have recruited a group of Chinese immigrants living in the community from the metropolitan area of Sydney who originally came from different parts of China (and other related regions) with various socioeconomic statuses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CADE-Q SV has proven to be both adaptable and useful for multiple language groups; therefore, it is a good instrument to consider for further adaptation to other languages and, now, other immigrant populations 24,49–51 . Given the rapid growth of the Chinese and other immigrant populations in global migration, it is increasingly crucial that instruments be translated and validated in suitable samples, including language groups that have different backgrounds 3,52 . For example, in this study, we have recruited a group of Chinese immigrants living in the community from the metropolitan area of Sydney who originally came from different parts of China (and other related regions) with various socioeconomic statuses.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, sensitivity analysis has shown that lower education levels and poor English proficiency were associated with poor disease-related knowledge in Chinese immigrants with CHD. Similarly, previous studies have also indicated that language and cultural barriers, as well as inadequate health literacy, have impeded Chinese immigrants with CHD from accessing health-related information and reliable resources, particularly those aimed at promoting healthy lifestyles of nutrition and exercise 6,7,25,52 . Therefore, there is a need to use CADE-Q SV (simplified Chinese version) to understand their disease knowledge levels and improve their knowledge and healthy behaviors in clinical practice aligned with the delivery of culturally sensitive patient educational interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of language proficiency extends beyond an individual’s social and economic participation. For instance, inadequate language proficiency directly leads to poor access to health information, health services, and communication with healthcare providers [ 9 , 10 , 11 , 12 ]. Additional information access barriers are related to cultural disparities between immigrants and healthcare providers in the host countries, and socio-economic disadvantages among migrant populations [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The MRT‐SCCI also argues that individuals' motivation to engage in self‐care is influenced by their ability to detect, interpret and manage symptoms, as well as their skills, experience, self‐efficacy, cognitive and functional abilities, social support and access to healthcare (Riegel, Jaarsma et al, 2019). Self‐care is not only a complex, multifactorial process but also a unique phenomenon influenced by each individual's reality (de Maria et al, 2022; de Maria, Ferro, et al, 2021; Zeng et al, 2021).…”
Section: Introductionmentioning
confidence: 99%